2011
DOI: 10.1063/1.3653820
|View full text |Cite
|
Sign up to set email alerts
|

Electron-emission yield under electron impact of ceramics used as channel materials in Hall-effect thrusters

Abstract: We report measurement of electron-emission yield (EEY) under the impact of electrons on materials of Hall-effect-thruster (HET) interest: BN, BN-SiO 2 , and Al 2 O 3 . The effects of the material aging (under electron irradiation) on the yield of BN and Al 2 O 3 are investigated. The EEY of BN grows with electron exposure, whereas that of Al 2 O 3 reduces. A simple analysis of our experimental results indicates that these variations are most likely because of surface and near surface composition changes caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…For a given primary energy, SEY increases with increasing angle of incidence θp. Concerning the wall temperature and electron irradiation dependences, s0 decreases while E * increases with electron irradiation and Tw (Tondu et al 2011 andBelhaj et al 2015), making the SEE process more negligible for hotter and highly irradiated surfaces.…”
Section: Conclusion: the Future Of Ht Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…For a given primary energy, SEY increases with increasing angle of incidence θp. Concerning the wall temperature and electron irradiation dependences, s0 decreases while E * increases with electron irradiation and Tw (Tondu et al 2011 andBelhaj et al 2015), making the SEE process more negligible for hotter and highly irradiated surfaces.…”
Section: Conclusion: the Future Of Ht Modelingmentioning
confidence: 99%
“…(c) (d) Fig. 21 (a) Total SEE yields as a function of primary electron energy (Tondu et al 2011) for some HT wall materials with (b) zoom view around the first crossover energy (indicated with arrows). (c) Components of SEY as a function of impact electron energy and (d) energy spectrum ds/dE of secondary electrons emitted by a beam of electrons with energy Ep=50 eV.…”
Section: Conclusion: the Future Of Ht Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of those modifications mainly depends on the material constituting the wall, the plasma temperature and the ions nature. Indeed, the SEE yield is characteristic of each material and is a function of the impinging electron energy 7,8 . Moreover, theoretical and numerical modeling showed that substantial changes in the sheath structure happen when the the emission overpasses a threshold that is dependent on the ion to electron mass ratio 3 .…”
Section: Introductionmentioning
confidence: 99%
“…e yield also significantly depends on the surface conditions. For aluminum with a native oxide, the emission yield [106] is significantly higher than for pure aluminum and corresponds to the yields found for dielectric materials [107,108]. erefore, in the third case, the yield for aluminum with a native oxide is used.…”
Section: Secondary Electron Emissionmentioning
confidence: 99%